2022
DOI: 10.1097/01.asw.0000803256.62585.d5
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy for Generalized Pruritus of Unknown Origin: Single-Center Experience

Abstract: OBJECTIVE:Phototherapy is a well-established therapy in dermatology. However, there is limited evidence regarding phototherapy for the treatment of generalized pruritus of unknown origin (GPUO). The objective of this study was to assess the efficacy and safety of narrowband ultraviolet B (NB-UVB) phototherapy in patients with GPUO. METHODS:Researchers conducted a retrospective review of the treatment outcomes of patients with GPUO who were treated with NB-UVB between 2004 and 2019 at their facility. RESULTS:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…In conclusion, phototherapy proved to be a rapid, effective, safe and inexpensive treatment modality to reduce itch and to improve itch‐related QoL in four out of five patients suffering from different itchy conditions. These data support previous studies 20,21,33,35,44,59,62 which demonstrated the continued importance of phototherapy in the era of targeted therapies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In conclusion, phototherapy proved to be a rapid, effective, safe and inexpensive treatment modality to reduce itch and to improve itch‐related QoL in four out of five patients suffering from different itchy conditions. These data support previous studies 20,21,33,35,44,59,62 which demonstrated the continued importance of phototherapy in the era of targeted therapies.…”
Section: Discussionsupporting
confidence: 91%
“…Our study population is also comparable to previous studies in terms of the number of participants, underlying skin diseases, age and gender distribution as well as itch intensity at baseline. [33][34][35] However, it is worth mentioning that some pruritic conditions commonly treated with phototherapy, such as uremic CP or chronic nodular prurigo, were not present in our population. As in other studies, NB-UVB was the most commonly used modality of phototherapy.…”
Section: Discussionmentioning
confidence: 79%
“…Although there have been no large, randomized, controlled trials investigating the antipruritic effects of phototherapy, there have been several retrospective studies. A retrospective chart review of 67 patients diagnosed with CPUO showed remission in 70% of patients after receiving NB-UVB phototherapy with no serious adverse side effects [101] . In another retrospective review of phototherapy in geriatric patients, of 12 patients with generalized pruritus, 80% achieved significant improvement with NB-UVB (excluding 2 patients who did not receive at least 8 sessions.)…”
Section: Phototherapymentioning
confidence: 98%